Covid-19 Medical Waste Management in the Perspective of Environmental Law - Aldira Mara Ditta Caesar Purwanto; Maria Novita Apriyani (Veteran Justice Journal, 2022)
Proper disposal of medical waste is one of the most important things in dealing with the Covid 19 pandemic. Over the last two years, the large number of Covid-19 cases caused by Delta and Omnicron variants has also led to an increase in medical waste generated by the use of masks and other personal protective equipment. This leaves homework for all of us, not just the government. This medical waste is generated not only in medical facilities but also in communities and homes. The waste in this pandemic is classified as Hazardous Waste and Toxic Waste (B3) and may be classified as Infectious Waste. The purpose of this study is to study the management of medical waste related to Covid19 from an ecological point of view so that it can effectively reduce the accumulation of waste that may have a natural impact on health promotion. Is to do. This investigation is a doctrinal/normative legal investigation that uses a legal approach. The data was collected through literature reviews and qualitatively analyzed. As a result of this study, the management of COVID-19 medical waste is regulated, and the treatment of medical facility waste and household waste is different. The purpose of this regulation is to reduce the increase in the amount of waste that can affect the environment and public health.